Amblysiphonella agahensis nov. sp., and Musandamia omanica nov. gen. nov. sp. (Porifera) from the Upper Tirassic of Oman - Senowbari-Daryan, Baba; Bernecker, Michaela (Zitteliana, 2010)
Two chambered sponges - A. agahensis nov. sp. and Musandamia omanica nov. gen., nov. sp. - from the Norian reefal limestones of Jebel Agah, southeast of the Musandam Mountains, Oman, are described. Both species are the first reported from the Triassic of the Arabian Peninsula. The fossil association is also mentioned.
UnivIS-Import:2017-12-18:Pub.2010.nat.dgeo.IGM.LP.amblys
Keywords: Porifera; Sphinctozoa; Amblysiphonella; Musandamia; Norian; Jebel Agah; Oman